[Rezension von: New testament apocrypha. Volume 3] - Bremmer, Jan N. (Early christianity, 2023)
Tony Burke, ed., New Testament Apocrypha: More Noncanonical Scriptures, vol. 3 (Grand Rapids, Mich.: Eerdmans, 2023), xxx + 651 pp., ISBN 978-0-8028-7793-2